Criss-crossing highways: Pacific travelling and dwelling in times of global warming. Issue 1 (1st April 2014) - Carter, Lynette
This article examines the challenges facing Pacific peoples from climate change. In particular it posits a framework for discussion around the notion of migration, identity and cultural sustainability that is couched in a repeated pattern of travelling and dwelling, a process that has been part of being a Pacific person for millennia. The article takes the position that evidence from oral tradition, history and contemporary times demonstrates that travelling is part of what it means to be a Pacific person. Climate change migration will be another contributor to this pattern of circular travelling and dwelling; departures and arrivals in the homeland. I examine the idea that the homeland is the pivot point for travelling and returning and as such is always the reference point for identity and nationhood. The future challenges for Pacific development and the impact of migration will be to find solutions from within the history, needs and aspirations of the Pacific peoples themselves; not in accepting the scenario of dependent and homeless climate refugees. This article is the first output from research into the wider challenges of the social impact of climate change migration on nationhood and identity and establishes a framework for thinking about solutions for the future that are informed from traditional ways to mitigate and adapt to challenge and change. I have taken the view that Aotearoa/New Zealand is part of the region and henceforth should be considered as part of the wider conversation of travelling and dwelling across the Pacific.